Beyond bullet points : using Microsoft PowerPoint to create presentations that inform, motivate, and inspire - Atkinson, Cliff (Redmond, Wash. : Microsoft Press, 2011)
A guide to using Microsoft PowerPoint describes how to use stories to create effective business presentations.
Includes index.
Keywords: Business presentations -- Graphic methods -- Computer programs; Multimedia systems in business presentations; Computer graphics; Business -- Computer software